BENTUK-BENTUK â€“ING DALAM JURNAL AUSTRALIAN JOURNAL OF LINGUISTICS VOLUME 23 - SAMPE, NOVENY AFISTA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This study entitled â€œBentuk-bentuk â€“ing dalam â€œAustralian Journal of Linguistics volume 23â€ is the study that focuses on morphosyntax analysis especially the forms and functions used in the article of the journal. It is an attempt to identify and analyze the forms and the functions of â€“ing in the Australian Journal. This research was done in several stages: preparation, data collection and data analysis. The data of â€“ing form were collected froms the article of the journal entitled â€œOrigami in a Hurricane: Current Challenges to Linguisticâ€ and were analyzed according to the theory of Aarts&Aarts (1982), Murphy (1994), Lado (2008) and Quirk (1972). The results of this study show the forms and the functions of â€“ing. There are 7 (seven) forms of â€“ing which are:Â  â€“ing clause that has explicit subject, -ing clause that has noÂ  explicit subject, -ing as a participle clause, -ing as an adjective, -ing as a present continuous tense, -ing as a past continuous tense, and -ing as a gerund. And there are 2 (two) functions of â€“ing which are : -ing that has functions as an adverbial, and â€“ing as a gerund which has functions as a subject, an object and an object of preposition. The outcomes of this study are expected to give contributions of the language development in linguistic studies especially in analyzing â€“ing form and are expected to help the students or readers to have more understanding about the â€“ing form. Â Keywords: Morphosyntax, form and function, -ing forms, -ing clause, Australian Journal of Linguistics vol.23